2008
DOI: 10.3163/1536-5050.96.4.012
|View full text |Cite
|
Sign up to set email alerts
|

Citation patterns of online and print journals in the digital age

Abstract: The citation of print-only journals by researchers with access to a library with a large print and electronic collection appeared to continue, despite the availability of potential alternatives in the online collection. Journals available in electronic format were cited more frequently in publications from the campus whose library had a small print collection, and the citation of journals available in both print and electronic formats generally increased over the years studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 10 publications
0
26
1
1
Order By: Relevance
“…They have been trying to establish why university communities, especially in Africa, have not embraced use of the electronic resources as expected. Findings have varied and have included issues of awareness (Bayugo and Agbeko 2007, Dilek-Kayaoglu 2008, Khan and Ahmad 2009, Salaam and Aderibidge 2010, Shahmohammadi 2012, attitudes and perceptions (De Groote 2008, Salaam and Aderibidge 2010, Tyagi 2012, promotion (Thanuskodi 2011, Vasishta andNavivoti 2011), and facilitating conditions as factors that influence the use of these resources (Ondari-Okemwa 2004, Bevilacqua 2005, Upadhyay and Chakraborty 2008, Salaam and Aderibidge 2010, Shahmohammadi 2012. Among the factors affecting electronic journals usage in universities, the issue of facilitating conditions has been prominent, especially in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…They have been trying to establish why university communities, especially in Africa, have not embraced use of the electronic resources as expected. Findings have varied and have included issues of awareness (Bayugo and Agbeko 2007, Dilek-Kayaoglu 2008, Khan and Ahmad 2009, Salaam and Aderibidge 2010, Shahmohammadi 2012, attitudes and perceptions (De Groote 2008, Salaam and Aderibidge 2010, Tyagi 2012, promotion (Thanuskodi 2011, Vasishta andNavivoti 2011), and facilitating conditions as factors that influence the use of these resources (Ondari-Okemwa 2004, Bevilacqua 2005, Upadhyay and Chakraborty 2008, Salaam and Aderibidge 2010, Shahmohammadi 2012. Among the factors affecting electronic journals usage in universities, the issue of facilitating conditions has been prominent, especially in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,19 The possible explanation for such citation advantage is that online articles are more likely to be cited because they are more readily read than their print-only counterparts. 9 Furthermore, other studies have indicated that faculty staff believed online journal articles allow for more timely literature searching as compared to the accessibility of the hardcopies via conventional subscriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Academic librarians keep abreast of new advancements and technologies related to research, while researchers and librarians have both developed a keen interest in figures to quantify research. Several bibliometrics topics were covered by librarians and information specialists (Bar-Ilan et al, 2012;Cronin, 2001;De Groote, 2008;Hood & Wilson, 2001;Jacso, 2008;Leydesdorff, 1998), and scholars from a variety of fields have also published extensively on topics related to the issues in bibliometrics (Abt, 2000;Boyack, Klavans, & Börner, 2005;Hall, 2014;Hicks, 2005;Hirsch, 2005;Schreiber, 2008;Vinkler, 2010). Scientists and librarians working in conjunction on citation analysis agree that the output indicators are just as good as the data input (Cronin, 2001;De Bellis, 2009;Jacso, 2008;Meho & Yang, 2007;Noruzi, 2005;West & McIlwaine, 2002).…”
Section: Scholarly Performance Indicators In Academic Librariesmentioning
confidence: 99%